Optical properties in the visible luminescence of SiO2:B2O3:CaO:GdF3glass scintillators containing CeF3 - J. M. Park (2018)
© 2017, The Korean Physical Society. CeF 3 -doped silicaborate-calcium-gadolinium glass scintillators, with the formula 10SiO 2 :(55-x)B 2 O 3 :10CaO:25GdF 3 :xCeF 3 , were fabricated by the melt-quenching technique. The doping concentration of the CeF 3 was from 0.00 mol% to 0.20 mol%. The optical properties of the CeF 3 doped glass scintillators were studied by using various radiation sources. The transition state of the CeF 3 -doped glass scintillators studied by using the absorption and photo-luminescence spectrum results. The X-ray, photo, proton and laser-induced luminescence spectra were also studied to understand the luminescence mechanism under various conditions. To understand the temperature dependence, the laser-induced luminescence and the decay component of the CeF 3 -doped glass scintillator were studied while the temperature was varied from 300 K to 10 K. The emission wavelength spectrum showed from 350 nm to 55 nm under various radiation sources. Also the CeF 3 -doped glass scintillator have one decay component as 34 ns at room temperature.